2014
DOI: 10.1002/ece3.994
|View full text |Cite
|
Sign up to set email alerts
|

Color expression in experimentally regrown feathers of an overwintering migratory bird: implications for signaling and seasonal interactions

Abstract: Plumage coloration in birds plays a critical role in communication and can be under selection throughout the annual cycle as a sexual and social signal. However, for migratory birds, little is known about the acquisition and maintenance of colorful plumage during the nonbreeding period. Winter habitat could influence the quality of colorful plumage, ultimately carrying over to influence sexual selection and social interactions during the breeding period. In addition to the annual growth of colorful feathers, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…As damage accumulates, the functional properties of feathers are compromised, and hence birds must replace them. Moreover, Tonra et al (2014) showed that both yearlings and adult males American redstarts Setophaga ruticilla regrew tail feathers with lower chroma, suggesting reduced carotenoid content. Because the costs of maintaining an incomplete plumage, most birds replace these accidentally lost feathers in a process called adventitious replacement (Willoughby et al 2002), which may impose yet other costs in terms of feather quality (Dawson et al 2000, Grubb 2006.…”
mentioning
confidence: 99%
“…As damage accumulates, the functional properties of feathers are compromised, and hence birds must replace them. Moreover, Tonra et al (2014) showed that both yearlings and adult males American redstarts Setophaga ruticilla regrew tail feathers with lower chroma, suggesting reduced carotenoid content. Because the costs of maintaining an incomplete plumage, most birds replace these accidentally lost feathers in a process called adventitious replacement (Willoughby et al 2002), which may impose yet other costs in terms of feather quality (Dawson et al 2000, Grubb 2006.…”
mentioning
confidence: 99%
“…In this species, coloration appears to have important signaling functions during both the breeding (Reudink, Marra, Boag, et al. (2009)) and nonbreeding seasons (Reudink, Studds, Kyser, Marra, & Ratcliffe, 2009; but see Tonra et al., 2014). The limited number of studies examining the potential for carryover effects to influence sexual selection by affecting ornament production is perhaps surprising given the immense body of literature on the function and evolution of plumage coloration.…”
Section: Discussionmentioning
confidence: 99%
“…, Tonra et al . ). This suggests that adventitious replacement is unable fully to restore the original properties of feathers, probably as a consequence of food constraints that typically do not occur during normal moulting periods (Tonra et al .…”
mentioning
confidence: 97%
“…This suggests that adventitious replacement is unable fully to restore the original properties of feathers, probably as a consequence of food constraints that typically do not occur during normal moulting periods (Tonra et al . ). The great majority of studies working on replaced feathers have traditionally analysed tail flight feathers (rectrices; e.g.…”
mentioning
confidence: 97%
See 1 more Smart Citation